HUKUM DAKWAH ISLAMIYAH DALAM PERSPEKTIF SOSIAL MASYARAKAT GORONTALO MASA KINI - Katili, Lukman D (Alhurriyah, 2014)
"Da'wah" is always associated with social science disciplines. Ideally, a preacher preaching that in applying the strategy to use the instruments of the social sciences to support the success of "Da'wah" that he doing Gorontalo people who have a philosophy Aadati hula-hula'a to syara'a, Syara'a hula-hula'a to the Book of Allah, since the arrival of Islam around the 15th century AD to the present, has undergone a "Da'wah's" transformation process of traditional methods to modern methods using effective media.